Association between high-density lipoprotein cholesterol and apolipoprotein A-I and severe acute pancreatitis: a case-control study. Issue 12 (December 2021) - Li, Yaling; Zheng, Rui; Gao, Feng; Wang, Li; Feng, Shuyi; Li, Jie; Huang, Zhiming
Abstract : Background: Evidence is limited concerning the association between serum concentrations of high-density lipoprotein cholesterol (HDL-C) and apolipoprotein A-I (APO A-I) and severe acute pancreatitis (SAP). This study was designed to explore whether HDL-C and APO A-I were independently correlated to SAP after adjusting for covariates. Methods: There were 1127 patients with acute pancreatitis who were recruited from a tertiary teaching hospital in Wenzhou from 1 January 2018 to 30 April 2020. The independent variables were baseline levels of HDL-C, and APO A-I collected within 24 h after admission. The dependent variable was the occurrence of SAP during hospitalization. Univariate and multivariate binary logistic regression were conducted to analyze the relationship between HDL-C and APO A-I and SAP. The receiver operating characteristic curve was applied to analyze the prediction power of lipid parameters and C-reactive protein for SAP. Results: The incidence of SAP was 11.5% among the 678 patients included in the final analysis. The serum levels of APO A-I and HDL-C were negatively related to SAP after adjusting for confounders with an odds ratio of 0.24 [95% confidence interval (CI): 0.06–0.95] and 0.16 (95% CI, 0.04–0.56), respectively. APO A-I (area under the curve = 0.69; 95% CI, 0.63–0.76) and HDL-C (area under the curve = 0.72; 95% CI, 0.66–0.79) showed higher predictive value for SAP compared with other lipid parameters. Conclusions: Decreased serum concentrations of HDL-C and APO A-I are associated with SAP after adjusting for covariates. Abstract : Supplemental Digital Content is available in the text.